Utilization Efficiency of Sewan Grass (Lasiurus sindicus) and Gr undnut (Arachis hypogaea)’ Haulm Based Feed in Rathi Calves - Mondal, B C; Yadava, N D; Singh, J P; Beniwal, R K (Annals of Arid Zone, 2016)
Ten Rathi female calves of about 8S.5kg body weight (BW)were rand mly divided into o’ groups and fed ad libitum sewan (Lasiurus sindicus) grass (Gl) and groundnut (Arac is hypogaea) haulm (G2) along with 0.5 kg concentrate mixture animar1[ dai1 to all the animals for 100 days. Average daily BW gains were 225.0Â±32.27and 421.0Â±26.77g in Gl (sewan’ grass fed) and G2 (groundnut haulm fed), respectively, where a DMI were 2.46Â±o.15’ kg and 3.06Â±o.OSper 100kg BWin Gl and G2, respectively. Digestibilit)nutrients in exp enta ar:umalswere 40.67Â±o.36,45.SSÂ±o.43, 44.82Â±o.33,46.25Â±2.75,61.79Â±1. 2,37.74Â±o.92 and 38)12Â±l,.27YIon Gl and 60.73Â±1.84,63.S3Â±1.696, 5.06Â±1.745, 0.62Â±2.06,61.55Â±2.8 1 6,49.06Â±2.07 and 53.4 Â±2l46%in G2,respectively,for dry matter (DM),organicmatter (OM),total Ci:arbohydrate (TCHO),’crude protein (CP), ether extract (EE),neutral detergent fiber (NDF), a4d detergent fibre (AOFr The digestible crude protein (DCP) and total digestible nutrients DN) values of the feed were 3.30 and 45.89%in Gl and 4.S6 and 57.34%in G2, respectivel Groundnut haulm -bas d feed was more palatable than sewan grass-based feed to Rat calves and supported body weight gain during experimental periods. Key wp*ds: Rathi calves, sewan grass, groundnut haulm, nutrient utilizatio